Construction of Shallow Surface States through Light Ni Doping for High‐Efficiency Photocatalytic Hydrogen Production of CdS Nanocrystals. Issue 1 (28th November 2013) - Li, Shuo; Zhang, Lijing; Jiang, Tengfei; Chen, Liping; Lin, Yanhong; Wang, Dejun; Xie, Tengfeng
Abstract Ni‐doped CdS nanowires were synthesized by a simple one‐step method. X‐ray diffraction, X‐ray photoelectron spectroscopy, and photoluminescence spectroscopy confirmed that light Ni doping can form shallow surface states due to the presence of substitutional Ni ions, and heavy Ni doping can form deep surface states due to the presence of interstitial Ni ions. Surface photovoltage spectroscopy and transient photovoltage measurements revealed that the shallow surface states can prolong the lifetime of the photogenerated charge carriers, whereas the deep surface states lead to recombination of the photogenerated charge carriers. The relationship between different surface states and the photocatalytic performance of CdS nanocrystals are discussed. The enhanced density of shallow surface states due to light Ni doping significantly promotes photocatalytic H2 production.